Building a postgraduate psychiatry training program in Liberia through cross-country collaborations: initiation stages, challenges, and opportunities - Ghebrehiwet, Senait; Ogundare, Temitope; Owusu, Micaela; Harris, Benjamin L.; Ojediran, Babawale; Touma, Mia; Durham, Michelle P.; Hook, Kimberly; Borba, Christina P. C.; Henderson, David C. (Frontiers in Public Health, 2023)
Background: About 80% of the nearly 2 billion people experiencing psychiatric conditions worldwide do not have access to quality, affordable mental health care. In Africa, there are 0.004 psychiatrists per 10,000 people, with the shortage exacerbated by a limited number of postgraduate psychiatry training opportunities. As of 2018, there were only two psychiatrists in Liberia. Methods: This paper aims to offer a framework for developing postgraduate (i.e., residency) psychiatry training in resource-constrained settings to disseminate best practices and lessons learned. This article describes the approach to developing the formal global academic partnership that supported the initiation of Liberia's first postgraduate psychiatry training program in July 2019. Results: Authors describe strengths, challenges, and opportunities for improvement in the planning and initiation stages of the postgraduate program. Key strengths of the program planning process include: 1) collaboration with a coalition of local and national stakeholders committed to improving mental health care in Liberia; 2) early procurement of quality video conferencing equipment and internet service to facilitate remote learning and broaden access to digital materials; and 3) leveraging of intra-continental partnerships for subspecialty training. Challenges experienced include: 1) navigating the intricacies of local political and administrative processes; 2) recruiting candidates to a medical specialty with historically lower salaries; and 3) the added burden placed on the limited number of local specialists. Identified opportunities include building a monitoring, evaluation, and learning (MEL) framework, further diversifying subspecialty areas of psychiatric and neurological training, and obtaining full accreditation of the postgraduate psychiatry program through the West African College of Physicians (WACP).The successful launch of the postgraduate psychiatry training program in Liberia is attributed to several factors, including a long-standing academic collaboration of over ten years and support for mental health capacity-building efforts at national and local levels.